(untitled) (Swiss Medical Weekly, 2018)
Head and neck squamous cell carcinoma (HNSCC) is a frequent tumour arising from multiple anatomical subsites in the head and neck region. The treatment for early-stage disease is generally single modality, either surgery or radiotherapy. The treatment for locally advanced tumours is multimodal. For recurrent/metastatic HNSCC palliative chemotherapy is standard of care. The prognosis is limited and novel treatment approaches are urgently needed. HNSCC evades immune responses through multiple resistance mechanisms. HNSCC is particularly characterised by an immunosuppressive environment which includes the release of immunosuppressive factors, activation, expansion of immune cells with inhibitory activity and decreased tumour immunogenicity. An in-depth understanding of these mechanisms led to rational design of immunotherapeutic approaches and clinical trials. Currently, only immune checkpoint inhibitors, namely monoclonal antibodies targeting the immune inhibitory receptor programmed cell death 1 (PD-1) and its ligand PD-L1 have proven clinical efficacy in randomised phase III trials. The PD-1 inhibitor nivolumab is the only drug approved for platinum-refractory recurrent/metastatic HNSCC. However, many more immunotherapeutic treatment options are currently under investigation. Ongoing trials are investigating immunotherapeutic approaches also in the curative setting and combination therapies using different immunotherapeutic approaches. This review article summarises current knowledge of the role of the immune system in the development and progression of HNSCC, and provides a comprehensive overview on the development of immunotherapeutic approaches.